IMPACT OF DIFFERENT MEDIA AND GENOTYPES IN IMPROVING ANTHER CULTURE RESPONSE IN RICE (Oryza sativa) IN BANGLADESH - Romana Siddique (European Scientific Journal, ESJ, 2015)
Rice is an important crop in Bangladesh.In vitro production of doubled haploid (DH) plants through anther-culture provides an efficient method for rapid production of homozygous lines. For this purpose, two different media MS and N6 supplemented with 1mg/L BAP +1mg/L 2,4- D+0.5mg/L NAA were evaluated for callus induction and green plant regeneration.Results showed that the highest percentages of calluses and green plants as a continuous process were obtained by N6 compared to MS. The best response to callus formation was obtained by BR48 and and minimum green plant obtained from OM576.